Carbonaceous Nanowire Supports for Polymer Electrolyte Membrane Fuel Cells. (14th September 2015) - Garzon, Fernando H; Wilson, Mahlon S.; Banham, Dustin; Ye, Siyu; More, Karren L.
Abstract : Carbohydrate-dye combinations were used to form ionically-linked soft templates for the formation of polypyrrole nanowire networks. High yields of nanostructured products were obtained using small amounts of low-cost carbohydrate and dye template materials, the majority of which remained encapsulated within the nanowires. Varying the concentration and the two-part ratio of the templates influenced the length and diameter of the nanofiber segments within the nanowire network. Pyrolysis of the nanowires yielded carbonaceous fibers containing nitrogen heteroatoms as well as convoluted graphitic domains well suited for supporting Pt nanoparticles. The resulting high density of nucleation sites enabled the formation of smaller Pt particles compared to commercial catalysts despite significantly higher support surface loadings.